3′-Daidzein Sulfonate Sodium Protects Against Chronic Cerebral Hypoperfusion-Mediated Cognitive Impairment and Hippocampal Damage via Activity-Regulated Cytoskeleton-Associated Protein Upregulation - Zeng, Qi; Huang, Zhihua; Zhang, Jiandong; Liu, Ruizhen; Li, Xiao; Zeng, Jing; Xiao, Hai (Frontiers in Neuroscience, 2019)
The learning and memory impairment caused by chronic cerebral hypoperfusion (CCH) is permanent and seriously affects the daily life of patients and their families. The compound 3'-daidzein sulfonate sodium (DSS) protects against CCH-mediated memory impairment and hippocampal damage in a rat model. In the present study, we investigated further the underlying mechanisms of this effect in the rat two-vessel occlusion (2VO) and the oxygen and glucose deprivation (OGD) primary hippocampal neuron models. The hippocampal expression of the activity-regulated cytoskeleton associated protein (Arc) following DSS administration was detected in vivo and in vitro and behavioral testing was used to investigate the role of Arc in the DSS-mediated rescue of CCH-induced neurotoxicity. DSS increased hippocampal Arc expression both in vivo and in vitro Arc overexpression increased and Arc knockdown decreased hippocampal neuronal densities in rat 2VO model, when compared to DSS treatment alone. Arc overexpression decreased and Arc knockdown increased apoptotic hippocampal neurons in rat 2VO and OGD primary hippocampal neuron models, when compared to DSS treatment alone. Arc overexpression enhanced and Arc knockdown inhibited the beneficial effect of DSS on 2VO-induced cognitive impairment. DSS restored the neuronal OGD-mediated phosphorylation decrease in protein kinase alpha (PKA), extracellular signal-regulated protein kinases 1/2 (ERK1/2) and cAMP response element binding protein (CREB), in vitro. PKA and ERK1/2 inhibition blocked the DSS-mediated effects on neuronal apoptosis and OGD-induced Arc downregulation. In conclusion, DSS protects against CCH-mediated cognitive impairment and hippocampal damage via Arc upregulation, which is activated by the PKA/CREB and ERK/CREB signaling pathways. Our study further confirms the potential use of DSS as an effective treatment for CCH-associated diseases.